The notion of cause in science and politics - Faure, Murray (University of the Free State, 2009)
English: This article explores some of the features and implications of causality and how the use of this contested concept may be understood and appraised as it applies to the world of politics and, in more detail, the scientific study thereof. In the teaching and learning of politics serious attention is seldom paid to the nature, implications, uses and limitations of causality as a fundamental ontological category in our quest for understanding and explanation. The article explores the conventional as well as some alternative notions of causality, and concludes with an appraisal of the significance of understanding causality.

Afrikaans: Hierdie artikel ondersoek sommige van die eienskappe en implikasies van kousaliteit jeens die politiek, en in die besonder die politieke wetenskap, en hoe die gebruik van hierdie betwisde konsep verstaan en beoordeel kan word. In die onderrig en die studie van die politiek word weinig aandag geskenk aan die aard, implikasies, gebruike en tekortkomings van hierdie fundamentele ontologiese konsep en hoe dit ons soeke na verstaan en verklaring raak. Die artikel ondersoek die konvensionele sowel as enkele alternatiewe sienings oor kousaliteit en bied by wsye van ’n gevolgtrekking ’n waardering oor die belangrikheid van kousaliteit.
Keywords: Politics; Political science; Learning of politics